Vascular peroxide 1 promotes ox-LDL-induced programmed necrosis in endothelial cells through a mechanism involving β-catenin signaling. (July 2018) - Zhang, Yin-Zhuang; Wang, Lei; Zhang, Jie-Jie; Xiong, Xiao-Ming; Zhang, Di; Tang, Xuan-Meng; Luo, Xiu-Ju; Ma, Qi-Lin; Peng, Jun
Abstract: Background and aims: Vascular peroxidase 1 (VPO1) plays a key role in mediation of cardiovascular oxidative injury. This study aims to determine whether VPO1 can promote programmed necrosis of endothelial cells and the underlying mechanisms. Methods and results: Human umbilical vein endothelial cells (HUVECs) were incubated with oxidized low-density lipoprotein (ox-LDL, 100 μg/mL) for 48 h to induce cell injury, which showed an elevation in cell necrosis (reflected by the increased propidium iodide (PI) positive-staining cells, LDH release and decreased cell viability), concomitant with an increase in programmed necrosis-relevant proteins including receptor-interacting protein kinase 1/3 (RIPK1/3), p-RIPK3 and mixed lineage kinase domain like (MLKL); these phenomena were attenuated by necrostatin-1(Nec-1) and RIPK3 siRNA. Meanwhile, VPO1 was up-regulated in ox-LDL-treated endothelial cells accompanied by a decrease in GSK-3β activity and p-β-catenin levels, and an elevation of β-catenin levels; these phenomena were reversed in the presence of VPO1 siRNA or hypochlorous acid (HOCl) inhibitor; replacement of ox-LDL with HOCl could also induce endothelial programmed necrosis and activate the β-catenin signaling; β-catenin inhibitor could also suppress ox-LDL-induced RIPK-dependent necrosis. In hyperlipidemic patients, the plasma level of VPO1 was obviously increased concomitant with an elevation in plasma levels of RIPK1, RIPK3 and MLKL, and they were positively correlated. Conclusions: VPO1 plays an important role in promotion of endothelial programmed necrosis under hyperlipidemic conditions through activation of β-catenin signaling. It may serve as a novel therapeutic target for prevention of endothelial dysfunction in hyperlipidemia. Graphical abstract: Highlights: Programmed necrosis occurred in ox-LDL-treated HUVECs. VPO1 exerts a key role in promotion of endothelial programmed necrosis. VPO1 promotes endothelial programmed necrosis through activation of β-catenin.